Targeted nanocarriers based on iodinated-cyanine dyes as immunomodulators for synergistic phototherapy. Issue 20 (17th April 2020) - Chi, Jinnan; Ma, Qingming; Shen, Zijun; Ma, Caiyun; Zhu, Wei; Han, Shangcong; Liang, Yan; Cao, Jie; Sun, Yong
Abstract : Photodynamic therapy (PDT), as one of the most powerful photo-therapeutic strategies for cancer treatment with minimum invasiveness, can effectively damage local tumor cells and significantly induce systemic antitumor immunity. Abstract : Photodynamic therapy (PDT), as one of the most powerful photo-therapeutic strategies for cancer treatment with minimum invasiveness, can effectively damage local tumor cells and significantly induce systemic antitumor immunity. However, current nanotechnology-assisted PDT-immunomodulators have either poor penetration for deep tumors or low singlet oxygen generation. Herein, we construct a novel theranostic nanocarrier (HA–PEG–CyI, HPC) by inducing the self-assembly of PEGylated CyI and attaching the ligand HA to its surface. The prepared HPC can be used as an ideal PDT-immunomodulator for synergistic cancer therapy. CyI is an iodinated-cyanine dye with enhanced singlet oxygen generation ability as well as excellent photo-to-photothermal and near-infrared fluorescence imaging properties. Under 808 nm laser irradiation, the prepared HPC can generate both reactive oxygen species (ROS) and elevate temperature which can subsequently result in apoptosis and necrosis at tumor sites. Moreover, the HPC-induced cell death can generate a series of acute inflammatory reactions, leading to systemic immunity induction and secondary death of tumor cells, which further results in reducing tumor recurrence. In vitro and in vivo results show that HPC can enhance the tumor targeting efficacy, generate ROS efficiently and exhibit a high temperature response under NIR irradiation, which working together can activate immune responses for synergistic phototherapy on tumor cells. Accordingly, the proposed multi-functional HPC nanocarriers represent an important advance in PDT and can be used as a superior cancer treatment strategy with great promise for clinical applications.